Land cover changes and greenhouse gas emissions in two different soil covers in the Brazilian Caatinga - Ribeiro, Kelly [UNESP] (2016)
The Caatinga biome covers an area of 844,453 km2 and has enormous endemic biodiversity, with unique characteristics that make it an exclusive Brazilian biome. It falls within the earth's tropical zone and is one of the several important ecoregions of Brazil. This biome undergoes natural lengthy periods of drought that cause losses in crop and livestock productivity, having a severe impact on the population. Due to the vulnerability of this ecosystem to climate change, livestock has emerged as the main livelihood of the rural population, being the precursor of the replacement of native vegetation by grazing areas. This study aimed to measure GHG emissions from two different soil covers: native forest (Caatinga) and pasture in the municipality of São João, Pernambuco State, in the years 2013 and 2014. GHG measurements were taken by using static chamber techniques in both soil covers. According to a previous search, so far, this is the first study measuring GHG emissions using the static chamber in the Caatinga biome. N2O emissions ranged from − 1.0 to 4.2 mg m− 2 d− 1 and − 1.22 to 3.4 mg m− 2 d− 1 in the pasture and Caatinga, respectively, and they did not significantly differ from each other. Emissions were significantly higher during dry seasons. Carbon dioxide ranged from − 1.1 to 14.1 and 1.2 to 15.8 g m− 2 d− 1 in the pasture and Caatinga, respectively. CO2 emissions were higher in the Caatinga in 2013, and they were significantly influenced by soil temperature, showing an inverse relation. Methane emission ranged from 6.6 to 6.8 and − 6.0 to 4.8 mg m− 2 d− 1 in the pasture and Caatinga, respectively, and was significantly higher only in the Caatinga in the rainy season of 2014. Soil gas fluxes seemed to be influenced by climatic and edaphic conditions as well as by soil cover in the Caatinga biome.